Digital Literature in France - Bouchardon, Serge (Dichtung Digital, 2012)
In this paper, I first retrace the filiations and the history of digital literature in France, emphasizing the various literary and aesthetic tendencies and the corresponding structures (groups, reviews). Then I focus on French digital literature communities. I notably give an account of a study that I did in 2004-2007 for the Centre Pompidou in Paris: I analyzed a socio-technical device (discussion list and website) called e-critures, dedicated to digital literature, with the hypothesis of the co-construction of a socio-technical device, a field and a community. I conclude on the possible characteristics of digital literature in France.
Keywords: digital literature; écriture et lecture numériques; history of digital literature